Discordance between plain coronary angiography and quantitative flow ratio in revascularization guidance. (14th October 2021) - Oikonomou, D; Gkini, K P; Terentes-Printzios, D; Gardikioti, V; Dima, I; Solomou, E; Xydis, P; Laina, A; Aznaouridis, K; Tsioufis, K; Vlachopoulos, C
Abstract: Background/Introduction: Functional coronary stenosis severity has been associated with less clinical adverse events compared with plain invasive coronary angiography in guiding revascularization. Quantitative flow ratio (QFR) has proven to be a reliable tool of functional assessment of coronary lesions. Purpose: To investigate the level of agreement between plain coronary angiography and QFR in guiding the decision to treat a coronary lesion. Methods: We retrospectively performed an offline QFR analysis in consecutive patients who underwent coronary angiography in a single center. Patients with referral for coronary artery bypass graft surgery were excluded. We aimed to measure QFR in all vessels of each patient. All vessels with calculated QFR were divided into four groups based on whether percutaneous coronary intervention (PCI) was performed and on the QFR result with a cut-off point <0.8 indicating revascularization: Group A (PCI+, QFR <0.8); group B (PCI−, QFR >0.8); group C (PCI+, QFR >0.8); group D (PCI−, QFR <0.8) (Figure 1). Results: We identified 785 patients with available coronary angiography satisfying the technical requirements of QFR software. QFR measurement in at least one vessel was feasible in 546 patients (70%). Mean age was 65.6 (±10.9) and 80% of patients were male. Acute coronary syndrome was the indication for coronary angiography in 36% of the cohort. QFR was calculated in 1193 vessels (∼51% of total vessels). In particular, QFR analysis was feasible in 448 (57%) left anterior descending (LAD), 457 (58%) left circumflex (LCX), and 288 (37%) right coronary arteries (RCA) coronary arteries. The most common reason for inability to calculate QFR was the absence of appropriate projections (30% of the missing cases). A mismatch in treatment strategy between coronary angiography and QFR result was detected in 151 (12.7%) vessels. In 78 (6.6%) cases PCI was performed while QFR was measured above 0.8 (group C). In 73 (6.1%) cases PCI was not performed while QFR was measured below 0.8 (Group D) (Figure 1). Among mismatch cases LAD was more likely to fall within group D whereas RCA was more often related with group C. Conclusion: Discordance between plain coronary angiography and quantitative flow ratio regarding the decision to perform or to defer PCI was found in a relatively high proportion among patients undergoing coronary angiography. Prognostic evidence is warranted to determine the clinical significance of the mismatch between the two methods. Funding Acknowledgement: Type of funding sources: None.